Comparison of Simultaneous Bilateral with Unilateral Total Knee Arthroplasty in Thabo Crown Prince Hospital - Wichan, MD, Woraphot (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: The propose of this study was to compare patient demographics and results between simultaneous bilateral total knee arthroplasty (SBTKA) and unilateral total knee arthroplasty (UTKA) in Thabo Crown Prince Hospital. All operations were performed by a single surgeon. Methods: 153 patients who underwent simultaneous bilateral total knee arthroplasty (SBTKA group, n = 48, 96 knees) and unilateral total knee arthroplasty (UTKA group, n = 105) between 1 January 2013 - 31 May 2017 were recruited. Both groups were compared for postoperative complication, rate of blood transfusion, need for intensive care unit (ICU) admission, length of stays, time from surgery to initial physical therapy and mortality rate. Results: Patients undergoing SBTKA were older than UTKA group (65 ± 8.6 VS 62.4 ± 7.6, p-value = 0.156), had higher proportion of female (87.50% VS 80%, p-value = 0.408), and higher frequency of having comorbid condition (81.25% VS 70.47%) but not significantly different (p-value > 0.05). The mean of length of hospital stay was 7.70 days for UTKA group and 8.40 days for the SBTKA group but there was no difference between two group (p-value = 0.17). The blood transfusion requirement was higher in the SBTKA group than in the UTKA group (4.2% VS 2.9%) but was not different between groups (p-value = 0.672). No significant differences in the time from surgery to initial physical therapy between two groups (p-value = 0.465). Superficial wound infection were occurred only 1 cases in both groups. No serious postoperative complication, no death or need for ICU admission were encountered in both groups. Conclusion: SBTKA seems to be safe procedure and is not associated with increase of surgical risk for patient in Thabo Crown Prince Hospital.